2021
DOI: 10.1002/ehf2.13271
|View full text |Cite
|
Sign up to set email alerts
|

Acute heart transplantation from mechanical circulatory support in a human immunodeficiency virus‐positive patient with fulminant myocarditis

Abstract: Since the establishment of highly active antiretroviral therapy, survival rates have improved among patients with human immunodeficiency virus infection giving them the possibility to become transplant candidates. Recent publications revealed that human immunodeficiency virus-positive heart transplant recipients' survival is similar to non-infected patients. We present the case of a 40-year-old human immunodeficiency virus infected patient, who was hospitalized due to severely decreased left ventricular functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…In cases without myocardial recovery, ECMO stabilizes and optimizes cardiogenic shock prior to semi-urgent cardiac transplantation [98]. Multiple case-reports of fulminant myocarditis [99,100] describe successful acute heart transplants in patients who could not be weaned off ECMO. Observational retrospective studies showed that although patients who receive transplant have a relatively high mortality rate, if they do receive a transplant, they have a very high survival rate.…”
Section: Veno-arterial Extracorporeal Membrane Oxygenation Weaningmentioning
confidence: 99%
“…In cases without myocardial recovery, ECMO stabilizes and optimizes cardiogenic shock prior to semi-urgent cardiac transplantation [98]. Multiple case-reports of fulminant myocarditis [99,100] describe successful acute heart transplants in patients who could not be weaned off ECMO. Observational retrospective studies showed that although patients who receive transplant have a relatively high mortality rate, if they do receive a transplant, they have a very high survival rate.…”
Section: Veno-arterial Extracorporeal Membrane Oxygenation Weaningmentioning
confidence: 99%